Determination of Formaldehyde in Different Brands of Perfumes by High Performance Liquid Chromatography - Sheikh, Warda; Naz, Narjis (Asian Journal of Chemistry, 2013)
In this study, formaldehyde was determined in different brands of perfumes available in local markets of Pakistan using high performance liquid chromatography (HPLC), with a pre-column derivatization with 2,4-dinitrophenylhydrazine. Thirty samples of perfumes were taken and their derivatives were prepared to analyze using a C18 column with 45 % acetonitrile solution and water (1:1 v/v) as mobile phase and detected at the wavelength of 345 nm. None of the perfumes labelled formaldehyde but the results showed that out of 30 perfumes, 21 of them confirmed formaldehyde release.